O controle inibitório em crianças e adolescentes bilíngues do Município de Curitiba- PR - Cristiano, Luana Breda (2018)
Studies on bilingualism have raised interest since the 1920s, but it is still instigating and without agreement among authors. At the beginning it way thought that bilingualism was related to intelligence, something discarded after years of study. In the 1980s, a new line of research began to investigate the impacts of bilingualism on executive functioning, and after some findings, authors suggested that inhibitory control seemed to be the domain that most benefited from bilingual experience. Subsequently, different studies around the world began to investigate the relationship between bilingualism and executive functions, from children to the elderly population, through early bilinguals to those with late learning. In research, the main tests used are Simon Task, Stroop and Flanker task, in which response time and reaction time are evaluated against incongruent (distracting) stimuli. But tests of working memory and language assessment also have great acceptance. In the present study, inhibitory control measures were evaluated in 22 children between 6 and 12 years of age, of both genders, living in Curitiba-PR, 11 monolingual (Portuguese) and 11 cradle bilinguals (English or French). of at least 3 hours per day each language. Due to the non-availability in Brazil of two of the above mentioned tools, the Five-Digit Test, Hayling, Stroop and Random Number Generation were used in all subjects. Absence of benefits with bilingual experience was identified. However in the descriptive statistics, it can be seen that bilinguals had greater accuracy in the responses and, although not statistically significant, there was better performance in the measure of interference of the Stroop test. Since the tests were not used pure measures of evaluation of inhibitory control, because they involve verbal components, the absence of advantages may have had an impact of the competition among these domains, since foreign research that shows advantages in bilinguals makes use of nonverbal measures. In addition, the low number of individuals made difficult by access to the sample prevents the generalization of the data, and the fact that such tasks are not computerized and depend on the reaction time of the evaluator, can also impact the effective recording of responses. Future research that minimizes the impacts of these variables may indicate more reliable results and contribute to the understanding of how bilingualism is expressed in the Brazilian population.